Management of Retrograde Peri-Implantitis Using an Air-Abrasive Device, Er,Cr:YSGG Laser, and Guided Bone Regeneration - Nikolaos Soldatos; Georgios E. Romanos; Michelle Michaiel; Ali Sajadi; Nikola Angelov; Robin Weltman (Case Reports in Dentistry)
Background. The placement of an implant in a previously infected site is an important etiologic factor contributing to implant failure. The aim of this case report is to present the management of retrograde peri-implantitis (RPI) in a first maxillary molar site, 2 years after the implant placement. The RPI was treated using an air-abrasive device, Er,Cr:YSGG laser, and guided bone regeneration (GBR). Case Description. A 65-year-old Caucasian male presented with a draining fistula associated with an implant at tooth #3. Tooth #3 revealed periapical radiolucency two years before the implant placement. Tooth #3 was extracted, and a ridge preservation procedure was performed followed by implant rehabilitation. A periapical radiograph (PA) showed lack of bone density around the implant apex. The site was decontaminated with an air-abrasive device and Er,Cr:YSGG laser, and GBR was performed. The patient was seen every two weeks until suture removal, followed by monthly visits for 12 months. The periapical X-rays, from 6 to 13 months postoperatively, showed increased bone density around the implant apex, with no signs of residual clinical or radiographic pathology and probing depths ≤4 mm. Conclusions. The etiology of RPI in this case was the placement of an implant in a previously infected site. The use of an air-abrasive device, Er,Cr:YSGG, and GBR was utilized to treat this case of RPI. The site was monitored for 13 months, and increased radiographic bone density was noted.